Credit Expansion in Emerging Markets : Propeller of Growth? - Garcia-Escribano, Mercedes (IMF Working Papers; Working Paper ;, 2015)
This paper explores the contribution of credit growth and the composition of credit portfolio (corporate, consumer, and housing credit) to economic growth in emerging market economies (EMs). Using cross-country panel regressions, we find significant impact of credit growth on real GDP growth, with the magnitude and transmission channel of the impact of credit on real activity depending on the specific type of credit. In particular, the results show that corporate credit shocks influence GDP growth mainly through investment, while consumer credit shocks are associated with private consumption. In addition, taking Brazil as a case study, we use a time series model to examine the role that the expansion and composition of credit played in driving real GDP growth in the past. The results of the case study are consistent with those found in the cross-country panel regressions.